The Holy Thief - Ryan, William (Pan Macmillan, 2010)
It's Moscow, 1936 and Stalin's Great Terror is beginning. In a deconsecrated Church, a young woman is found dead. Committed to uncovering the truth behind this gruesome murder, Captain Alexei Dimitrevich Korolev, from the CID of the Moscow Militia, enters the realm of the Thieves, who run Moscow's underworld.